Estudio Bibliométrico de la Revista de Psicología de la Pontificia Universidad Católica del Perú (2015 - 2024) - Palma Mamani, Adriana Elizabeth (2025)
This bibliometric study analyzes the articles published in the PUCP Journal of Psychology between the years 2015 and 2024, with the purpose of characterizing psychological production in the last decade. To do this, 280 documents were reviewed, including theoretical articles and empirical research, using a data sheet, with a quantitative, descriptive and longitudinal methodology, as is typical of bibliometrics. The results show that there are several notable trends at a theoretical and methodological level. The articles that have been published most frequently come from countries such as Peru, Argentina, Brazil, Chile, Mexico and Spain. There is a notable increase in female authorship of signed works as well as greater internationalization. Furthermore, studies on social psychology and those that follow a cognitive model continue to be the most predominant. Other areas of psychology that achieved representativeness were educational psychology and organizational psychology; with a prominent use of psychological tests for data collection and taking samples from adolescents and adults preferably.